A Review of Methods Applied to Study Airborne Biocontaminants inside Aircraft Cabins - Sandro Tavares Conceição; Marcelo Luiz Pereira; Arlindo Tribess (International Journal of Aerospace Engineering)
Indoor-cross infection of expiratory contaminants is still a concern, worsened by the SARS outbreak in 2003 and recent cases of influenza strains (H1N1, avian flu, etc.). A variety of methods to study the airborne spread of expiratory contaminants have been worked out, including the use of tracer gas, particle generators, and CFD simulations. In this context, the main objective of this work is reviewing methods to evaluate airborne dispersion of contaminants, more specifically those related to cross infection of expiratory droplets inside aircraft cabins. This literature review provides guidance in developing methods and choosing equipment for future studies.This study gathers knowledge developed so far in a common source, serving as a guideline for researchers who work in this area.